Respuesta :

Answer:

Step-by-step explanation:

a). Given function is y = [tex]\frac{1}{2}x^3-2x+1[/tex]

At x = -3,

y = [tex]\frac{1}{2}(-3)^3-2(-3)+1[/tex]

y = -13.5 + 6 + 1

y = -6.5

For x = -2,

y = [tex]\frac{1}{2}(-2)^3-2(-2)+1[/tex]

y = -4 + 4 + 1

y = 1

For x = 2

y = [tex]\frac{1}{2}(2)^2-2(2)+1[/tex]

y = 4 - 4 + 1

y = 1

Therefore, table for the given function will be,

x       -3       -2       -1        0        1         2

y     -6.5       1      2.5      1       -0.5     1  

b). From the table given in part (a) we find the points lying on the graph are (-2, 1), (-1, 2.5) and (2, 1).

    These points justify the graph (C)

Therefore, graph (C) will be the answer.

ACCESS MORE